Automatic tuning of linearly tunable high-Q filters - Karşilayan, Aydin I.; Huang, Sung-Ling; De Lima, Jader A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
A new tuning scheme for linearly tunable high-Q filters is proposed. The tuning scheme uses the phase information for both frequency and Q factor tuning, therefore no relationship between filter's passband magnitude and Q is required. To reduce the simulation overhead, operation of the tuning circuit is verified on a symbolic filter whose parameters were derived from the transistor level circuit. At 10 MHz, for a desired Q of 20, simulated frequency and Q tuning errors are 0.3% and 1.7%, respectively.